2016
DOI: 10.1200/jco.2016.34.2_suppl.192
|View full text |Cite
|
Sign up to set email alerts
|

Combined Akt and MEK pathway blockade in pre-clinical models of enzalutamide-resistant prostate cancer.

Abstract: Despite recent improvements in patient outcomes using newer androgen receptor (AR) pathway inhibitors, treatment resistance in castrate resistant prostate cancer (CRPC) continues to remain a clinical problem. Co-targeting alternate resistance pathways are of significant interest to treat CRPC and delay the onset of resistance. Both the AKT and MEK signaling pathways become activated as prostate cancer develops resistance to AR-targeted therapies. This pre-clinical study explores co-targeting these pathways in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Gene expression analysis has indicated that enzalutamide modulates the expression of factors involved in angiogenesis, cell adhesion, and apoptosis. 7 Using an in vitro enzalutamide-resistant PC model, Toren et al 8 observed that enzalutamide also activates the survival kinases protein kinase B (AKT) and mitogen-activated protein kinase kinase (MEK), as part of the enzalutamide resistance machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression analysis has indicated that enzalutamide modulates the expression of factors involved in angiogenesis, cell adhesion, and apoptosis. 7 Using an in vitro enzalutamide-resistant PC model, Toren et al 8 observed that enzalutamide also activates the survival kinases protein kinase B (AKT) and mitogen-activated protein kinase kinase (MEK), as part of the enzalutamide resistance machinery.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical models have shown a compensatory relationship between PI3K and MAPK signaling in prostate cancer, 28 and that simultaneous inhibition of PI3K and MAPK signaling can inhibit mCRPC. [29][30][31] MAPK signaling can be targeted with MEK inhibitors, such as trametinib and cobimetinib, which are approved for BRAFmutated melanoma and KRAS/BRAF-mutated colorectal cancer. 32 Although anecdotal, a heavily pretreated mCRPC patient treated with trametinib elicited a durable clinical response.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al observed that loss of function of PCDH7 significantly reduced tumor development, prolonged survival, and diminished phospho‐activation of ERK1/2 in lung cancer mouse model. Recent study by Torren et al shows reduced tumor growth of Enzalutamide resistant PCa cells by combined inhibition of AKT and ERK compared to monotherapy. Furthermore, these findings suggest that PCDH7 inhibition could diminish AKT and ERK activation and reveal future investigation of PCDH7 based therapeutics.…”
Section: Discussionmentioning
confidence: 99%